Pengaruh Pemberian Pupuk Kimia NPK dan Pengaturan Jarak Tanam Terhadap Pertumbuhan dan Produksi Tanaman Kacang Panjang (Vigna sinensis L.) - Sormin, Siti Yuli Meilanda; Hasibuan, Andri Syahputra; Tanjung, Akhir Abadi; Sari, Risna Maya; Triyanto, Yudi (UNIVERSITAS LABUHANBATU, 2024)
The purpose of this research was to determine the effect of fertilizer and plant spacing on the growth and yield of long beans. Plant spacing and fertilizer application were carried out to obtain optimal results. This research was conducted on the land of Balimbing Tonga, Padang Bolak Julu, North Padang Lawas Regency, North Sumatra from May to July. The research was conducted using the Experimental method Factorial Randomized Block Design with 2 factors and 3 replications. The results showed that the dose of fertilizer and planting distance did not have asignificant effect on fruit weight and root weight. The results of the Analysis of Variance (ANOVA) test showed a significant interaction between the fertilizer treatments. There is a significant interaction between fertilizer treatment and spacing on the parameters of plant height, number of fruits, number ofleaves, and root weight. Keywords: string beans, npk fertilizer, plant spacing, production